Pelatihan Pengembangan Aplikasi Web Menggunakan Laravel Untuk Siswa SMKN 1 Sukawati Gianyar Bali - Ni Made Satvika Iswari; Eddy Muntina Dharma (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
This community service activity aimed to enhance the web development skills of students at SMKN 1 Sukawati through Laravel framework training. Although students were familiar with HTML and CSS, they lacked experience with modern PHP-based frameworks like Laravel, which are essential in today’s industry. The program was carried out in four phases: requirement analysis, coordination, training, and evaluation. Conducted on April 15, 2025, the face-to-face training included theory, hands-on practice in creating CRUD (Create, Read, Update, Delete) applications, and discussion. To measure learning outcomes, a pre-test and post-test were given. The average score increased from 83.9 to 90, showing a clear improvement in students’ technical skills and understanding. The activity also sparked interest and motivation among students to further explore web development. This training is expected to be a foundation for developing digital competencies and industry-relevant portfolios. Continued training and mentoring are recommended for sustainable skill growth.